1988
DOI: 10.1016/0048-9697(88)90428-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical pollution on the activities of hepatic xenobiotic metabolizing enzymes in fish from the river rhône

Abstract: Polychlorobiphenyl (PCBs) levels and hepatic xenobiotic metabolizing enzyme activities were measured in fish from three locations of the River Rhône to study the consequences of a constant loading of PCBs from a PCB incineration plant. Our results show that levels of PCBs and enzyme activities were higher in fish living downstream from the plant than in fish from two locations upstream, suggesting enzyme induction by PCBs (known to be potent inducers in laboratory conditions). Enzyme activities were studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…The total concentration of P450 a sum parameter, frequently used and quite easy to determine, could be a screening method of contamination, mainly to polynuclear aromatic hydrocarbons (PAH), and planar polychlorinated biphenyls (PCB). Although some authors have shown that this method was less sensitive to induction than specifically inducible isoenzymes or their respective enzyme activities (Monod et al 1988, Lange et al, 1998. Standardizing analytical techniques is a crucial step that must be carried out before field application of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The total concentration of P450 a sum parameter, frequently used and quite easy to determine, could be a screening method of contamination, mainly to polynuclear aromatic hydrocarbons (PAH), and planar polychlorinated biphenyls (PCB). Although some authors have shown that this method was less sensitive to induction than specifically inducible isoenzymes or their respective enzyme activities (Monod et al 1988, Lange et al, 1998. Standardizing analytical techniques is a crucial step that must be carried out before field application of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…After a peak in scientific interest (for example Monod et al, 1988) and public attention at the end of the eighties, the PCB pollutions of the Rhône River drew no attention until 2005. In 2004 in the Grand Large, many dead birds were found and fishing was forbidden.…”
Section: Spatial and Temporal Contextmentioning
confidence: 99%
“…Parmi les systèmes proposés par les écotoxicologues comme indicateur possible de pollution figurent les monooxygénases à cytochrome P450 (LINDSTRÔM-SEPPÀ et al, 1985 ;PAYNE et al, 1987 ;VINDIMIAN et GARRIC, 1989 ;NARBONNE et al, 1991) et à un degré moindre, les transferases (ANDERSSON et al, 1985 ;JEDAMSKI-GRYMLAS et al, 1995). De nombreuses publications démontrent que des polluants majeurs de l'environnement tels que les hydrocarbures aromatiques polycycliques (HAP) ou les polychlorobiphényles (PCB) sont des inducteurs puissants du CYP1 A, un des isozymes du cytochrome P450 (MONOD et al, 1988 ;GOKS0YR et FÔRLIN, 1992 ;HAASCH et ai, 1993). Cependant, la plupart de ces travaux ne considérant que les enzymes hépatiques mettent en oeuvre des doses importantes de polluants ou utilisent des voies d'exposition telles que l'injection intrapéritonéale très éloignées de la situation de terrain.…”
Section: Introductionunclassified